The impact of maturity regulation on high interest rate lenders and borrowers - Benston, George J. (Journal of Financial Economics, 1977)
The State of Maine recently imposed an additional regulation on the maturity of small loans offered by finance companies, presumably to protect the consumer. The effectively restricted the maturity of these high interest rate loans to 36 months. Within five years, the number of licensees (finance company offices) declined from 116 to 24. Within another five years, all of these lenders had completely ceased operations. Hypotheses on the effect and value to consumers of the regulation are stated operationally and tested empirically. This study includes estimation of the loan companies' cost function, (accounting) profit rates and output and a survey of the individuals directly affected by the demise of the companies. The analysis indicates (1) that the maturity restriction made ordinary operations unprofitable, (2) why this occurred, and (3) that half of the consumers did not obtain funds elsewhere.